Review on Upcoming Innovative Technology in Big Data - Therasa, M; M. Poonkuzhali, S; Santhana Joyce, M; Annie Shery, S (International Journal of Engineering and Technology, 2018)
This paper is a survey of the big data idea, its measurements, its design correlation between the prior idea and the most recent, the capacity conceivable i.e. the databases and starting point of enormous information. The social database, having unbending pattern, has been winning since quite a while yet it is hard to store the unstructured information in social database. The unstructured information has principally message nature or is as logs. Here comes the idea of No SQL databases. Enormous Data is little information with huge information estimate.Â Â